Implementation of Temulawak (Curcuma xanthorrhiza Roxb.) Extract Nanoemulsion on Production Performance and Income Over Feed Cost in Broiler Chickens - Al Kurnia, Dyanovita; Dewi Ratih Ayu Daning; luki amar; Utari (Jurnal Ternak, 2025)
This study aimed to evaluate the effect of temulawak extract nanoemulsion (Curcuma xanthorrhiza Roxb.) supplementation in drinking water on the production performance and Income Over Feed Cost (IOFC) of broiler chickens. The study utilized 100 broiler chickens of the Loghman MB 202 Platinum strain, which were randomly assigned into four treatments: P0 (control), P1 (4 mg/kg body weight), P2 (6 mg/kg body weight), and P3 (8 mg/kg body weight), with five replications per treatment. Data were analyzed using one-way ANOVA followed by Duncan’s multiple range test. The results showed that the P2 treatment (6 mg/kg) produced the best performance, with a final body weight of 1,677 g/bird, feed intake of 202.83 g/bird, and the lowest feed conversion ratio of 1.34. The highest IOFC was also observed in P2, amounting to Rp11,367/bird. In conclusion, supplementation of temulawak extract nanoemulsion at a dose of 6 mg/kg body weight effectively improved production performance and IOFC in broiler chickens and is recommended for implementation.